2019
DOI: 10.1002/ptr.6376
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone alleviates renal interstitial fibrosis and kidney dysfunction in rats with unilateral ureteral obstruction

Abstract: Unilateral ureteral obstruction (UUO) causes severe renal tubulointerstitial fibrosis. Because of many pharmacologic properties of thymoquinone (TQ), in this study, the effects of TQ against kidney fibrosis and dysfunction were investigated in rats with UUO. Forty male Wistar rats were divided into five groups: Sham operated, UUO, and the animals with UUO treated with losartan, captopril, or TQ. Collagen IV and transforming growth factor (TGF)‐β1 expressions, interstitial fibrosis, histological changes, and ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Indeed, captopril decreased the concentration of soluble collagen in the LV of rats with combined continuous light and L-NAME-induced hypertension ( Simko et al, 2010 ), attenuated LV collagen deposition in SHR ( Zhao et al, 2015 ), and reduced LV fibrosis in mice with transverse aortic constriction ( Zhang et al, 2019 ) and Sprague-Dawley rats with L-NAME-induced hypertension ( Sonoda et al, 2017 ). Similarly, in kidneys captopril reduced interstitial renal fibrosis in neonatal dogs with partial urethral obstruction (PUO) ( Shirazi et al, 2007 ), ameliorated fibrosis in rats with PUO ( Shirazi et al, 2014 ), and downregulated interstitial fibrosis in rats with unilateral ureteral obstruction ( Hosseinian et al, 2019 ). In line with these data, our results show reduced intraglomerular, tubulointerstitial, and perivascular collagen accumulation and renal hydroxyproline concentration after 6 weeks of captopril administration in lactacystin-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, captopril decreased the concentration of soluble collagen in the LV of rats with combined continuous light and L-NAME-induced hypertension ( Simko et al, 2010 ), attenuated LV collagen deposition in SHR ( Zhao et al, 2015 ), and reduced LV fibrosis in mice with transverse aortic constriction ( Zhang et al, 2019 ) and Sprague-Dawley rats with L-NAME-induced hypertension ( Sonoda et al, 2017 ). Similarly, in kidneys captopril reduced interstitial renal fibrosis in neonatal dogs with partial urethral obstruction (PUO) ( Shirazi et al, 2007 ), ameliorated fibrosis in rats with PUO ( Shirazi et al, 2014 ), and downregulated interstitial fibrosis in rats with unilateral ureteral obstruction ( Hosseinian et al, 2019 ). In line with these data, our results show reduced intraglomerular, tubulointerstitial, and perivascular collagen accumulation and renal hydroxyproline concentration after 6 weeks of captopril administration in lactacystin-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…TQ, as a natural product phytochemical, has the potential to control cancer cell proliferation as well as metastasis (Li et al, 2017; Mostofa et al, 2017). In addition, a growing body of evidence suggests that TQ has inhibitory effects on organ fibrosis (Bai et al, 2014; Hosseinian et al, 2019; Pourgholamhossein et al, 2016). For example, Bai et al (2014) found that TQ can reduce hepatic fibrosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%